FAKTOR INTERNAL DAN PENGARUHNYA TERHADAP RISK PERCEPTION DAN EXPECTED RETURN PERCEPTION - Ryanda Bella Rengku (STIE Perbanas Surabaya, 2012)
It is important for the business to understand their internal factors. By doing so, they can make use of then for increasing their return and minimizing the risk. This study aims to explore the effect of internal factors on risk perception and expected return perception. Internal factors in this study consist of overconfidence, emotion, mental accounting and experience. Samples were drawn from investors in Surabaya who invested their fund in land and property, gold, mutual fund, and deposit. To test hypotheses, this study employs classical assumption test and multiple regression analysis Based on the analysis, it found that internal factors have a significant effect on risk perception simultaneously but have no significant effect on expected return perception. Besides that, it was found that mental accounting is the only internal factor which significantly influenced the risk perception but partially while experience significantly influenced the expected return perception also partially. Finally, investor perception of risk and expected return indicated a positive correlation.